Pengelompokkan kabupaten/kota di kalbar dengan metode biplot terstandarisasi - Mokhsan, Masykuri (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
In principle, a biplot is a graphical methode in two dimensional visual. The information of the biplot result contains the objects that represent the rows of data matrix and the observed variables that represent the columns of data matrix. Many of the observed variables in social, economics, politics and any other studies have the different measurement scaling. That different measurement scaling must be standardized.. The standardized biplot analysis is part of the biplot analysis that has been developed to solve the different of measurement scaling between variables. The weight for the standardized biplot use standard deviation.The Standardized Biplot Scaling method in this study is applied on the regency’s classification in West Kalimantan case based on Human Development Index variables. The HDI’s variables such as Life expectacy Rate, Expected Years of Schooling, Mean Years School and Purchasing Power Parity have different measurement scaling. Before standardization with standard deviations, each value of the HDI variable is centralized by reducing the value of each HDI variable to the average value of each HDI variable.